2013
DOI: 10.1063/1.4788932
|View full text |Cite
|
Sign up to set email alerts
|

Quenching-induced circumvention of integrated aging effect of relaxor lead lanthanum zirconate titanate and (Bi1/2Na1/2)TiO3-BaTiO3

Abstract: Articles you may be interested inElectric-field-temperature phase diagram of the ferroelectric relaxor system (1−x)Bi1/2Na1/2TiO3−xBaTiO3 doped with manganese

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The unpoled curves from all samples are similar in shape, exhibiting a broad maximum in the dielectric permittivity close to 300°C and a low‐temperature shoulder. It was proposed recently that these two anomalies arise from the presence of two types of polar nanoregions . Poling the samples by applying an electric field of 4 kV/mm at room temperature for 5 min changes the shape of the curves significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The unpoled curves from all samples are similar in shape, exhibiting a broad maximum in the dielectric permittivity close to 300°C and a low‐temperature shoulder. It was proposed recently that these two anomalies arise from the presence of two types of polar nanoregions . Poling the samples by applying an electric field of 4 kV/mm at room temperature for 5 min changes the shape of the curves significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ time-dependent XRD profiles for BNT–5BT at 70 °C (figure 7(c) inset) shows that the gradual development of long-range ordering domains, especially in the initial 2 h, were consistent with the time period of the modulus valleys. After the ‘stepwise increase’, the modulus becomes saturated with time evolution, indicating that the isothermal transition is nearly complete and an ageing effect becomes dominant [5053]. …”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the dielectric permittivity profiles are best‐fitted by assuming multi‐Debye relaxation or at least more than one relaxation mechanism . The coexistence of frozen and dynamic PNRs as well as PNRs with different symmetries have also been proposed. These models have been supported by identifying all the contributing mechanisms to the temperature‐dependent permittivity based on peak deconvolution techniques .…”
Section: Introductionmentioning
confidence: 99%